2004
DOI: 10.1128/jb.186.4.1158-1164.2004
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Associated Flagellum Formation and Swarming Differentiation inBacillus subtilisAre Controlled by theifmLocus

Abstract: Knowledge of the highly regulated processes governing the production of flagella in Bacillus subtilis is the result of several observations obtained from growing this microorganism in liquid cultures. No information is available regarding the regulation of flagellar formation in B. subtilis in response to contact with a solid surface. One of the best-characterized responses of flagellated eubacteria to surfaces is swarming motility, a coordinate cell differentiation process that allows collective movement of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
39
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 40 publications
5
39
0
Order By: Relevance
“…Plates were incubated for up to 24 to 48 h at 37°C, and swarm cell differentiation was analyzed as previously described (36,37). For microscopic examination of the cells, samples were obtained by slide overlaying on isolated colonies.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Plates were incubated for up to 24 to 48 h at 37°C, and swarm cell differentiation was analyzed as previously described (36,37). For microscopic examination of the cells, samples were obtained by slide overlaying on isolated colonies.…”
Section: Methodsmentioning
confidence: 99%
“…The behavior of a Bacillus subtilis ifmP mutant (PB5249) isolated from the laboratory strain PB1831 was recently described (37). Like other laboratory strains tested for swarming motility, PB1831, although motile, was nonswarming and did not produce flagella when transferred from liquid onto solid media.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study (20) also demonstrated swarming associated with a mutation leading to hyperflagellation, under conditions where the parental laboratory strain normally failed to swarm. However, other studies have described forms of swarming in B. subtilis apparently independent of flagella or surfactin (6,12), (14).…”
mentioning
confidence: 99%